Hungarian Monitoring, 4 May 1990 . [Magyar rádiófigyelő], 1990. május 4 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Report about German reunification - Mitterrand-Thatcher meeting - Baltic independence movements Domestic Affairs: - The new parliamentary committees begin their work - The Patriotic Electoral Coalition continues its activity as a non-parliamentary opposition - Károly Grósz interview about documents from the Kádár legacy - The Open Skies conference was unsuccessful - Iliescu's interview with Radio Free Europe - Előd Kincses's name deleted form the list of senatorial candidates Economy: - Hungarian Democratic Forum (MDF) measures to promote the market economy - The Common Market approves of the structural changes in the Hungarian economy - National Association of Cooperatives dissolved - Field-trip to the Gabčíkovo-Nagymaros hydroelectric power plant - Order from a Swedish shipping concern to the Óbuda shipyard - Bankruptcy at the Budapest Land Registry Office - On the need for the Debrecen airport Külpolitika: - Riport a német egyesülésről - Mitterrand-Thatcher találkozó - A balti népek függetlenségi törekvéseiről Belpolitika: - Megkezdik működésüket az Országgyűlés új bizottságai - A Hazafias Választási Koalíció parlamenten kívüli ellenzékként folytatja munkáját - Grósz Károly beszél a Kádár hagyatékból származó dokumentumokról - Eredménytelen az Nyitott Égbolt konferencia - Iliescu interjút ad a Szabad Európa Rádiónak - Romániában törlik Kincses Elődöt a szenátorjelöltek közül Gazdaság: - Az MDF a piacgazdaságot elősegítő lépésekről - A Közös Piac hozzájárulása a magyar gazdaság szerkezeti átalakításához - Föloszlott a SZÖVOSZ - Helyszíni szemle a bősi erőműnél - Svéd hajózási vállalat megbízása az Óbudai Hajógyárnak - Fizetésképtelen a Fővárosi Földhivatal - A debreceni repülőtér szükségességéről